Advances in understanding nitrogen flows and transformations: gaps and research pathways. (December 2014) - Richards, Karl; Fenton, Owen; Watson, Catherine; MÜLLER, C.; CLOUGH, T. J.
SUMMARY The nitrogen (N) cycle is one of the best studied elemental cycles. However, the N flows and transformations, in particular in aggregated soils, at small scales and in plant–soil systems are not yet fully understood. Analytical and molecular techniques are now available to address N dynamics at small scales. The methodological advances should go hand in hand with the development of suitable mathematical models addressing the small scale and the full complexity of the many interacting effects. The importance of denitrification within the N cycle is highlighted and used as an example of the progress achieved in recent times. Research gaps and possible research pathways are outlined.